1999
DOI: 10.1007/bf02784398
|View full text |Cite
|
Sign up to set email alerts
|

Selenium content of milk and milk products of Turkey. II

Abstract: Selenium content of 1028 milk and milk products of Turkey are presented in this study. The selenium content of human milk (colostrum, transitional, and mature milk), various kinds of milk [cow, sheep, goat, buffalo, paper boxes (3%, 1.5%, 0.012% fat), bottled milk, condensed milk (10% fat), mineral added milk (1.6%), and banana, strawberry, and chocolate milk] and milk products (kefir, yogurt, Ayran, various cheese, coffee cream, ice cream, butter, margarine, milk powder, and fruit yogurt) in Turkey were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Selenium was detected in 37 samples at a mean concentration higher than those in other studies [24,26,32,[58][59][60][61][62][63]. Thirty samples showed levels above the allowed limit.…”
Section: Resultsmentioning
confidence: 57%
“…Selenium was detected in 37 samples at a mean concentration higher than those in other studies [24,26,32,[58][59][60][61][62][63]. Thirty samples showed levels above the allowed limit.…”
Section: Resultsmentioning
confidence: 57%
“…Selenium is essential in trace amounts because it is a cofactor for several enzymes. However, its intake above the RDI may lead to blind staggers or alkalosis. , The concentration of this mineral in milk depends on its intake, especially from feedstuff. In countries where soils are poor in Se, the milk tends to have lower concentrations of this element. , In CPS where mineral supplements are commonly used, greater amounts of Se in the milk were detected.…”
Section: Discussionmentioning
confidence: 99%
“…This tendency is also true for Alberta, where soils rich in selenium, otherwise known as seleniferous soils, are very common [46]. Of note, excessive amounts of Se intake might cause various adverse effects [47,48]. Given that the raw milk in Alberta has lower concentrations of Se than its RDI (80%), it should be concluded that Alberta milk is safe for consumption with regards to Se content.…”
Section: Discussionmentioning
confidence: 99%